Industrial policy in the chemical industry in the context of economic sanctions against Russia - D. L. Frolov (Вестник университета, 2024)
The high importance of the chemical industry for the Russian economy in the socio-economic and foreign trade aspects causes increased attention to this industry. The need to provide all production, household and agricultural areas with products and raw materials supplied from chemical enterprises poses the task of reducing dependence on imports, which has developed over the past decades for most commodity items. The negative effect of import dependence became apparent after the introduction of anti-Russian sanctions back in 2014 and significantly intensified in 2022. These events have accelerated the work towards self-sufficiency in key chemical products. The study highlights the main stages of developing the program measures on import substitution, the evolution of some target indicators values and its implementation degree. The current state of the chemical industry in the country has been showed, its bias towards export-oriented industries assessed (fertilizers, synthetic rubber, ammonia, polymers, tires production). The attention to low-tonnage chemistry has decreased, which led to the deficit of its domestic production and the imports growth. The article studies the state of exports and the balance of trade in the main chemical products produced and consumed in Russia.